Structural changes in employment in old industrial regions of Ukraine - Mikhail Popov; Oleg Nabokov (European Regional Science Association (ERSA), 1998)
The formation of independent economy in Ukraine and its transition to the market is going under the low competitiveness of its main productive complexes and worn-out fixed capital. That will cause undesirable structural changes, which will be and already is associated with structural unemployment. These and similar issues are the main subject of the paper. The principle of full employment is being realized in Ukraine at present. A very low rate of unemployment, about 2-3 percent, has been shown by the official statistics of the country. It is quite obvious that there is a hidden unemployment and the large number of lay out people will appear soon, and first of all in basic industries. Eastern Ukraine, called Donbass, is exactly the region with such an economy. More than 30 percent of population of the region work for coal and steel industries. There are following tools elaborated in the course of the study and discussed in details in the paper to overcome the problem: * tax exemptions for priority sectors, for investment in socially important projects (employment, social infrastructure development, R&D), for specific geographical entities (underdeveloped districts, territories with high level of unemployment, settlements with ecological hazards); * setting up associations of enterprises to concentrate investment resources on socially important and economically profitable projects of the region's restructuring; * creation of the Fund for Regional Development and the Bank for Restructuring and Economic Development of Donbass which are aimed at financial support of investment projects of economic restructuring; * direct budget investments in different sectors, large industrial companies which are very important for the region.
Keywords: 330